Sarjana Teknik Industri Kualitas, Tantangan, dan Prospeknya Dalam Era Perdagangan Bebas - Matthias Aroef (The Institute for Research and Community Services, Institut Teknologi Bandung, 1996)
The world is undergoing a very rapid change in almost all aspects of life. So does Indonesia. Being a sub system in this changing world, Indonesia must adjust itself to fit to the future world condition. According to the General Agreement on Trade and Tariffs, the General Agreement on Trade in Services, a new World Trade Organization will be developed. Competition in this new world trade will be international in nature even in the domestic environment, and is perceived to become more and more competitive. It might develop into a cut throat competition.The Indonesian nation that is still a traditional agrarian society with feudal characteristics is changing towards an Industrial and information society in a short time. This requires a socio -cultural change partly already experienced by the urban population. The slowly changing traditional part of the plural society must be given greater speed, and this paper proposes a corporate approach. At the same time a slower process, but more basic in nature, should be handled by the educational institutions.New values and norms and new ways of doing things must be developed in the new Indonesian individual, such as appreciation of value of time , to like change, be more dynamic, more creative and innovative; be more entrepreneurial, more professional, achievement oriented, and competitive; always strive for better - qualitatively and quantitatively, for improvement, and for progress.This article considers also the changes that are needed in engineering education. The design of the curricula should incorporate contents that develop the new characteristics in the engineer for the future. They shou ld be world class engineers. Since such change should start as early as possible in the formation of the engineer, the curricula of the primary and secondary education should also be redesigned. It becomes a gigantic change process that must be carried out. All parties of the domestic system should take part in it.Since competition does not occur in the business world only, but will happen also in the professions, the competitiveness of the individuals must also be strengthened. Thus the whole national system must change, including the government, the business, and the individual. The change should be completed as early as in the year 2003, when the Asean Free Trade Area comes into effect, and become stronger by the year 2010 when the gates of the advanced countries are opened, and become very strong by the year 2020 when the gates of the developing countries should be opened.